Effect of the simulated digestion process on the chlorogenic acid trapping activity against methylglyoxal. Issue 1 (19th December 2022) - Colombo, Raffaella; Paolillo, Mayra; Frosi, Ilaria; Ferron, Lucia; Papetti, Adele
Abstract : The in vitro simulated gastrointestinal process strongly affected the 5- O -caffeoylquinic acid capacity to trap methylglyoxal and its resulting antiglycation activity. Abstract : Chlorogenic acids are hydroxycinnamic derivatives widespread in food or food by-products, known for their antioxidant effects and ability to interfere with the formation of advanced glycation end products (AGEs). AGEs are potential glycotoxins involved in age-related disorders, such as diabetes, cardiovascular diseases, and neurological disorders. The ability of chlorogenic acids to inhibit AGE formation under physiological conditions needs further investigation other than the in vitro assays. Therefore, in this study, the capacity of 5-caffeoylquinic acid (5-CQA) to effectively trap methylglyoxal (MGO), an AGE precursor compound also present in daily consumed food, was investigated by evaluating 5-CQA and MGO metabolic fate when subjected to digestion. Two different in vitro digestion approaches (static based on the Infogest protocol and dynamic based on a novel millifluidic gastrointestinal model) were set up and the samples collected at different steps of the static and dynamic processes were analyzed by a validated RP-HPLC-DAD method. The obtained results indicated that the gastrointestinal process strongly affected the 5-CQA capacity to trap MGO and its resulting antiglycation activity. Therefore, preliminary investigation using advanced in vitro tests, particularly dynamic approaches, should always be performed to predict the effect of the digestion process on the potential bioactives present in food, food by-products, or plant extracts.